ANALISIS POTENSI ASSET DAERAH SEBAGAI SUMBER PENDAPATAN ASLI DAERAH DI KOTA JAYAPURA - Transna Putra Urip (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2016)
The purposes of this research were to analyse potentialities of local markets and public transportation terminals as Local-Generated Revenue Sources and the effectiveness and efforts to optimize Local-Generated Revenues. This research was conducted in Jayapura Municipality. The research variables were facilities in the markets and terminals, terminal levy, payments frequency, and actual revenue from the markets and terminals. A quantitative approach was employed using potentials components and effectiveness ratios which later being analyse descriptively. The study showed an increase of propensity in the markets’ actual growth of revenues in an average of 11.97% and trends of the terminals’ levies growth in an average of -11.70%. The potential revenues from terminals’ levy were 4.088.502.000 IDR and 1.312.488.000 IDR. Thus, the total potential revenue was 5.400.990.000 IDR. The effectiveness level of actual revenues from markets fees reached 19.30 per cent and the actual terminals levies was 18.64 per cent. Hence, the total effectiveness level of markets and terminals fees was 19.18 per cent. Efforts were the improvements of local officers’ qualities, systems, administrations and working procedures, the corrective planning of local markets and terminals as well as assertive actions. Legal efforts were necessary to shed light on land ownership's to the local markets. Keywords: Levy, Markets, Terminals, Potential, Effectiveness, Facilities, Tariff